An antipyrine based fluorescence "turn-on" dual sensor for Zn2+ and Al3+ and its selective fluorescence "turn-off" sensing towards 2, 4, 6-trinitrophenol (TNP) in the aggregated state. Issue 11 (27th September 2019) - Dey, Sudipto; Maity, Ashim; Shyamal, Milan; Das, Debasish; Maity, Samir; Giri, Prabhat Kumar; Mudi, Naren; Samanta, Shashanka Shekhar; Hazra, Paresh; Misra, Ajay
Abstract : A 2, 6-diformyl- p -cresol (DFC)-4-amino antipyrine (AP) based dual signaling fluorescent Schiff base ligand (DFCAP) is found to exhibit colorimetric and fluorescence turn on selective sensing towards metal ions, Zn 2+ and Al 3+ . Abstract : A 2, 6-diformyl- p -cresol (DFC)-4-amino antipyrine (AP) based dual signaling fluorescent Schiff base ligand (DFCAP) is found to exhibit colorimetric and fluorescence turn on selective sensing towards metal ions, Zn 2+ and Al 3+ . It also exhibits a significant aggregation induced emission (AIE) phenomenon by controlling the water–THF solvent ratio which provides robust green emissive fluorogenic aggregates with well-defined morphologies. Turn-on fluorescence enhancements as high as 195 fold and 168 fold in methanol for Al 3+ and Zn 2+ at 480 nm and 508 nm, respectively, were noticed. The binding constants and stoichiometry determined from the fluorescence titration data are K = 7.63 × 10 4 M −1 and 3.42 × 10 4 M −1 and 1 : 1 complexation for both Al 3+ and Zn 2+ respectively, supported by Job's method. DFCAP shows high sensitivity towards the detection of Zn 2+ and Al 3+ ions with very low detection limit values of ca . ∼21 nM and 30 nM respectively. Besides by applying its attractive AIE feature, the green emissive hydrosol functions as a good chemosensor with high sensitivity for a selected explosive TNP through ground state complexation with a LOD value of ca . ∼1.74 μM and especially a high Stern–Volmer quenching constant of ca . ∼4.14 × 10 5 M −1 . For instant 'naked eye' response for the trace detection of TNP in the solution state, we fabricated a simple paper strip that could detect TNP on-site in a fast, inexpensive and simple way.